The Role of Organizational Structure in Project Management - Cut Nizma; Rehulina Bangun; Benhur Benhur; Cahyoginarti Cahyoginarti; Muhammad Zuardi (Jurnal Syntax Transformation, 2024)
Organizational structure has a significant impact on the effectiveness and efficiency of project implementation, as well as the management of the resources involved. By exploring various project management theories and organizational structure concepts, this research aims to investigate how the selection and implementation of an organizational structure can influence project performance. This research uses literature analysis and case study methods to identify key factors that influence the role of organizational structure in project management. The findings show that an appropriate organizational structure can improve coordination, communication, and decision-making in project teams. Conversely, a mismatch between organizational structure and project needs can hinder progress and create obstacles that are difficult to overcome. The results of this research provide valuable insights for project management stakeholders, including project leaders, senior managers, and project team members. By understanding the critical role of organizational structure, practitioners can make more informed and strategic decisions when designing and implementing their projects. Managerial implications and recommendations for further research are also discussed to deep understanding of the relationship between organizational structure and project management.